Artificial intelligence as an asset for the improvement of decision-making cycle in military operations - Pavić Aleksandar M.; Jelić Dragan R.; Đokić Miodrag S. (Војно дело)
The command-and-control system during the decision-making process in modern military operations, in addition to traditional methods, is increasingly based on the processing, analysis and interpretation of large amounts of information, which is partly a consequence of the use of modern technologies and changing operational environment. Among other things, the speed and dynamism of modern conflicts require quick decisions based on complex information. Managing such a large volume of information and making timely decisions can be a major challenge for commanders unless they have appropriate tools and adequate support. The use of artificial intelligence can be one of the potential solutions to the said challenge, because it can significantly optimise and speed up the decision-making process in modern military operations. The subject of this paper refers to defining the determinants, challenges and possibilities for the application of artificial intelligence in decision-making process in military operations. During the research, the method of content analysis and comparative method were applied, to eventually draw conclusions using the techniques of analysis and synthesis, and create a model of a possible place and role of artificial intelligence in the command system in military operations. The research results are presented within the framework of a functional model of one of possible ways to use artificial intelligence in the decision-making process. The model shows the possibility of artificial intelligence, together with humans, to be a significant factor in the decision-making process that will ensure supremacy in the process of making decisions. It can be concluded that the automation of the processes and the increase of autonomy in command using artificial intelligence will improve the decision-making process and certainly contribute to making future military operations more efficient and effective, as well as safer.